2018
DOI: 10.1016/j.jmmm.2017.08.070
|View full text |Cite
|
Sign up to set email alerts
|

On the interpretation of Mössbauer spectra of magnetic nanoparticles

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…But it can be noted that the broad asymmetric lines in the Mössbauer spectra observed at 200 K ( Fig. 3(a) and (b)) are typical for magnetic fluctuations governed by an interaction field arising from interparticle interactions [81]. Additionally we can conclude from the observed splitting of the spectra at 200 K that the cores are still thermally blocked, although it is worth mentioning that at 295(5) K they are clearly superparamagnetic on the Mössbauer time scale of ≈ 1 ns ( Fig.…”
Section: A Structural and Magnetic Pre-characterizationmentioning
confidence: 95%
“…But it can be noted that the broad asymmetric lines in the Mössbauer spectra observed at 200 K ( Fig. 3(a) and (b)) are typical for magnetic fluctuations governed by an interaction field arising from interparticle interactions [81]. Additionally we can conclude from the observed splitting of the spectra at 200 K that the cores are still thermally blocked, although it is worth mentioning that at 295(5) K they are clearly superparamagnetic on the Mössbauer time scale of ≈ 1 ns ( Fig.…”
Section: A Structural and Magnetic Pre-characterizationmentioning
confidence: 95%
“…The pre-factor τ 0 is generally taken as 10 −9 − 10 −10 s, although it is sensitive on several parameters such as the particle size, temperature and dipolar interactions. 17,18 In Eq. (2), η is the viscosity of the surrounding medium and D h is the hydrodynamic diameter of the particle, including surrounding surfactant and/or depletion layer.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have been focused on understanding the influence of the particle sizes on the magnetic properties of hematite. These studies have shown that the particle size of α − Fe 2 O 3 nanoparticles has a significant impact on the magnetic properties, in particular on the Morin transition, the Néel temperature and superparamagnetic relaxation of the nanoparticles [43,46]. Consequently, synthesis methods and systems where the size of magnetic nanoparticles can be changed in a controllable manner are the most useful for studying the above-described effects.…”
Section: Introductionmentioning
confidence: 99%